Pengaruh Edukasi Anemia dengan Media Monomia (Monopoli Anemia) Terhadap Pengetahuan pada Siswi SMA Negeri 5 OKU - Rizkika Putri Amiza; Arnati Wulansari; Tina Yuli Fatmawati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Anemia is a condition where the hemoglobin (Hb) level in the blood is lower than normal. In general, the factors that cause anemia in young women are lack of knowledge regarding balanced nutritional intake patterns, restrictions on food consumption, and non-compliance with consuming blood supplement tablets (TTD). The aim of this research was to determine the effect of anemia education using monomia media (Monopoly Anemia) on the knowledge of female students at SMA Negeri 5 OKU. This type of research is quantitative research using the Pre-Experimental method with a One Group Pre Test and Post Test Design, collecting data by conducting pre-tests and post-tests and providing education with the monomia game (Monopoly Anemia). The total sample was 30 young women. Data analysis in the study used Univariate and Bivariate analysis using the Wilcoxon test to determine the effect of anemia education using monomia media (Monopoly Anemia) on the knowledge of female students at SMA Negeri 5 OKU. The research results showed that the average percentage of Pre-test knowledge was in the poor category, 17 female students (56.7%), while the average post-test knowledge was in the good category, 30 female students (100%). There was an effect of providing education using monomia (Monopoly Anemia) (p= 0.000). In this study it can be concluded that there was an increase in knowledge between the Pre Test and Post Test after being given education using monomia (Monopoly Anemia) to female students at SMA Negeri 5 OKU. It is recommended that teenagers increase their knowledge about anemia by seeking information on the prevention and control of anemia.